Preparing Healthful Ethnic Foods - Linda B. Bobroff; R. Elaine Turner (EDIS, 2012)
Eating a variety of nutrient-rich foods helps you get the nutrients you need to look and feel your best. One tasty way to increase variety in your food choices is to include ethnic foods like Chinese, Mexican, Italian, Greek, and others. How do you know that you are making healthy choices when you eat these foods? This revised 3-page fact sheet was written by Linda B. Bobroff and R. Elaine Turner, and published by the UF Department of Family, Youth and Community Sciences, June 2012.